2019
DOI: 10.12688/f1000research.18139.1
|View full text |Cite
|
Sign up to set email alerts
|

Emerging novel agents for patients with advanced Ewing sarcoma: a report from the Children’s Oncology Group (COG) New Agents for Ewing Sarcoma Task Force

Abstract: Ewing sarcoma is a small round blue cell malignancy arising from bone or soft tissue and most commonly affects adolescents and young adults. Metastatic and relapsed Ewing sarcoma have poor outcomes and recurrences remain common. Owing to the poor outcomes associated with advanced disease and the need for a clear research strategy, the Children’s Oncology Group Bone Tumor Committee formed the New Agents for Ewing Sarcoma Task Force to bring together experts in the field to evaluate and prioritize new agents for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 103 publications
2
64
0
2
Order By: Relevance
“…14 improving EFS, our analysis did not identify a significant association of early tumor response with OS, a theme observed in other solid tumors that highlights the limits of conventional cytotoxic chemotherapy regimens. 23 Further augmentation of therapy for metastatic Ewing sarcoma must be investigated via incorporation of novel targeted or biological agents, 24 or the addition of low-dose metronomic maintenance therapy as successfully implemented recently for rhabdomyosarcoma. 25 A unique aspect of our cohort is the selective administration of WLI, a practice based on early reports of survival in Ewing sarcoma patients treated at our institution who cleared pulmonary lesions and did not receive WLI.…”
Section: Discussionmentioning
confidence: 99%
“…14 improving EFS, our analysis did not identify a significant association of early tumor response with OS, a theme observed in other solid tumors that highlights the limits of conventional cytotoxic chemotherapy regimens. 23 Further augmentation of therapy for metastatic Ewing sarcoma must be investigated via incorporation of novel targeted or biological agents, 24 or the addition of low-dose metronomic maintenance therapy as successfully implemented recently for rhabdomyosarcoma. 25 A unique aspect of our cohort is the selective administration of WLI, a practice based on early reports of survival in Ewing sarcoma patients treated at our institution who cleared pulmonary lesions and did not receive WLI.…”
Section: Discussionmentioning
confidence: 99%
“…While oncogenic gene fusions involving transcription factors remain largely undruggable (Knott et al , 2019), clinical trials using larotrectinib, a kinase inhibitor targeting gene fusions involving NTRK1 /2/3, have shown promising results and could offer a strategy for the treatment of NTRK ‐fusion‐positive sarcomas (Doebele et al , 2015; Fig 3). In addition, DNA minor groove‐binding agents in DNA, such as trabectedin or mithramycin, have been described as potent inhibitors of EWSR1‐FLI1‐mediated transcription with anti‐tumor potential (Bailey et al , 2019; Harlow et al , 2019). A recent clinical trial showed that mithramycin was too toxic at the dose required to inhibit EWSR1‐FLI1 (Grohar et al , 2017).…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…Currently, there is a multi-center phase 2 trial of palbociclib monotherapy in Spain for patients who have advanced sarcomas with elevated expression of CDK4 (NCT03242382). Moreover, CDK4/6 inhibitors such as palbociclib are recognized as high priority agents by the Children's Oncology Group for testing in metastatic, relapsed Ewing sarcoma [215].…”
Section: Cdk-targeted Anti-cancer Therapymentioning
confidence: 99%